Cytokine Storm in Pathogenesis of COVID-19 Complications - Olga V. Rasputniak; Tetiana I. Gavrilenko; Olena A. Pidgaina; Liudmyla M. Shnaider; Oleksandr M. Lomakovskyi; Sviatoslav A. Kalashnikov (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To explore the current literature and key findings concerning the cytokine storm contribution to pathogenesis of COVID-19 complications and mortality, and summarize clinical and pathologic features of cytokine storm in COVID-19 patients.A cytokine storm is a hyperinflammatory state secondary to excessive production of cytokines by deregulated immune system. It manifests clinically as an influenza-like syndrome, which can be complicated by multi-organ failure and coagulopathy, leading in most severe cases even to death. Cytokine storm has recently emerged as key aspect in COVID-19 disease, as affected patients show high levels of several key pro-inflammatory cytokines, some of which also correlate with disease severity.The current review describes the role of critical cytokines in COVID-19-mediated cytokine storm. Key findings of the studies are provided further. A cytokine storm is associated with COVID-19 severity and is also a crucial cause of death from COVID-19. Impaired acquired immune responses and uncontrolled inflammatory innate responses may be associated with the mechanism of cytokine storm in COVID-19. Cytokine storm is defined as acute overproduction and uncontrolled release of pro-inflammatory markers, both locally and systemically. In COVID-19 patients, pyroptosis triggers the release of proinflammatory cytokines and affects macrophage and lymphocyte functions, causing peripheral lymphopenia. Cytokine storm is characterized by a clinical presentation of overwhelming systemic inflammation, hyperferritinemia, hemodynamic instability, and multi-organ failure. The cytokine storm clinical findings are attributed to the action of pro-inflammatory cytokines like interleukin-1, interleukin-6, tumor necrosis factor alpha, vascular endothelial growth factor.